Phenomenological Analysis of BPJS Biometric Validation Barriers in AMC Hospital Inpatient Admission - Alda Rizma; Desy Widyaningrum (International Journal of Health Sciences, 2026)
BPJS Kesehatan uses biometric validation through fingerprint scanning and the Face Recognition Identification System (FRISTA) to prevent fraud in patient registration; however, technical scanning failures may prolong inpatient registration waiting times. This qualitative study, using an inductive descriptive phenomenological approach, aimed to analyze in depth how biometric validation barriers are managed from the perspectives and direct actions of medical record admission officers at AMC Hospital. Data were collected through semi-structured interviews with two admission officers, selected by purposive sampling using strict inclusion and exclusion criteria as the entire operational population responsible for escalation and with data saturation achieved, as well as non-participant observation and document review. The findings show that admission officers perform four main roles: identifying technical barriers, including fingerprint-only failure, FRISTA-only failure, and double biometric failure; executing an escalation reporting workflow to the Team Coordinator and subsequently to the Head of Medical Records for manual V-Claim approval based on the recommendation of the physician in charge of care; providing de-escalation communication to reduce anxiety among patients' families; and maintaining registration efficiency in accordance with the Minimum Service Standard (≤ 15 minutes).